THE ROLE OF HOMEROOM TEACHERS IN PROCESSING THE EMOTIONS OF CLASS V STUDENTS, MIS MARDIYATUL ISLAMIYAH MEDAN - Mutiara Murni Harahap; Assyfa Ramadhina; Rahmi Fadiah Nasution; Syahril Ramadhan Nasution; Bani Amirul (Publikasi Inspirasi Indonesia, 2024)
The role of homeroom teachers is very important in processing emotions in students, homeroom teachers have a significant influence on the learning motivation and learning outcomes of their students. The role of homeroom teacher is very dominant in classroom management and teaching ability of a teacher. Teachers who have duties as homeroom teachers have professional competence so as to create effective, efficient learning, and can overcome problems in classroom management. This study aims to provide an overview of the role of homeroom teachers in processing emotions in elementary school children. The research method used is a descriptive qualitative method using data collection techniques in the form of observation, documentation, and literature study. This research was conducted at MIS Mardliyatul Islamiyah Medan with the subject of researching grade V students and teachers at the school. The role of homeroom teachers is very important in increasing student learning motivation so that the learning process can run well.